Legitimate differences : interpretation in the abortion controversy and other public debates - Warnke, Georgia (University of California Press, 1999)
Legitimate Differences challenges the usual portrayal of current debates over thorny social issues including abortion, pornography, affirmative action, and surrogate mothering as moral debates. How can it be said that our debates oppose principles of life to those of liberty, principles of liberty to those of equality, principles of equality to those of fairness, and principles of fairness to those of integrity, when we as Americans share all the.